New Documented Records of the Mesopelagic Fish Valenciennellus tripunctulatus (Sternoptychidae) in the Strait of Messina and a Review of Its Mediterranean Occurrences - Chiara Bacchiani; Giovanni Ammendolia; Sergio De Matteo; Mauro Cavallaro; Emanuela Fanelli; Pietro Battaglia (Fishes, 2024)
The constellation fish, Valenciennellus tripunctulatus, is a small mesopelagic teleost typically found in equatorial and temperate waters worldwide, although the species has been also rarely recorded in the Mediterranean Sea (less than 20 specimens from the available literature since 1918). The Mediterranean records have been documented for the Strait of Messina, the southern Tyrrhenian Sea, the Ligurian Sea and the Adriatic Sea. The present paper offers an updated review on the occurrence of V. tripunctulatus in the Mediterranean basin and provides data on three new specimens, collected in the Strait of Messina between April 2010 and March 2024. Furthermore, we also report information from two individuals found in March 1992 and February 2017, respectively. Overall, the standard length of these specimens ranged from 24.1 to 28.2 mm, whereas weight varied from 0.18 g to 0.20 g. Morphometric and meristic data were reported, and this analysis revealed few differences between examined individuals in the number of PV (ventral series anterior to pelvic fin base) and AC (from anal fin origin to caudal fin base) photophore series. The relationship between total length and standard length (SL = 0.75 × TL + 2.98), total length and head length (HL = 0.17 × TL + 1.47) and standard length and head length (HL = 0.23 × SL + 0.88) showed high correlation values. Considering the lack of data on this species in the Mediterranean, updating morphometric, meristic, biological, ecological and distribution information is very important for taxonomic purposes and useful in understanding the characteristics of the regional population and eventual differences between Mediterranean stock(s) and those from other oceanic areas.